Meningkatkan Kreativitas Dan Keterampilan Teknologi Calon Guru Melalui Pelatihan Pembuatan E-Book Berbasis Canva - Syarqiyah, Rosyidatus; Alifiani, Alifiani; Fuady, Anies (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2025)
This article aims to describe the implementation and outcomes of a community service program designed to enhance the creativity and technological skills of pre-service teachers through training on the development of interactive e-books using Canva. The program was initiated in response to the limited ability of students to optimally utilize Canva’s interactive features for designing innovative and applicable digital learning media. The community service method employed was training and mentoring based on a hands-on practice approach. The program was conducted through three main stages: needs analysis, training implementation, and evaluation. The participants were fifth-semester students of Nurul Jadid University, Probolinggo. Data were collected using a Likert-scale questionnaire and an assessment rubric for the e-book products. The data were analyzed using descriptive quantitative techniques to examine participants’ responses and the quality of the developed e-books. The results indicate that the majority of participants provided positive responses to all aspects of the training. The program contributed to improvements in participants’ understanding of Canva, creativity in designing interactive e-books, and self-confidence in developing and utilizing digital learning media. It can be concluded that training on interactive e-book development using Canva is effective in improving the technological skills and creativity of pre-service teachers and in supporting their readiness to meet the demands of 21st-century education